Technology Transfers for Climate Change - May Elsayyad; Florian Morath (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper considers investments in cost-reducing technology in the context of contributions to climate protection. Contributions to mitigating climate change are analyzed in a two-period model where later contributions can be based on better information, but delaying the contribution to the public good is costly because of irreversible damages. We show that, when all countries have access to the new technology, countries have an incentive to invest in technology because this can lead to an earlier contribution of other countries and therefore reduce a country's burden of contributing to the public good. Our results provide a rationale for the support of technology sharing initiatives.
Keywords: H41; Q52; D62; D83; F53; 330; private provision of public goods; environmental public goods; technology sharing; uncertainty; irreversibility